Exploration of CRISPR-Cas9 Gene Editing System Utilization for Targeted Induction of Apoptosis in Cancer Cells - Resti Ariani; Eka Cahya Muliawati; Zola Efa Harnis (Science Journal Get Press, 2026)
The CRISPR-Cas9 gene editing system represents a powerful approach for precision targeting of genetic determinants involved in cancer cell survival. This study evaluated the ability of CRISPR-Cas9 to induce apoptosis in cancer cells through targeted disruption of anti-apoptotic genes. Acute myeloid leukemia (HL-60 and KG-1) and anaplastic thyroid cancer (8505C and C643) cell lines were used to knockout BIRC5 (survivin) and MADD using specific single-guide RNAs. Efficient genome editing was achieved, with indel formation exceeding 50% across all models. Targeting BIRC5 and MADD significantly reduced cell viability to 39.8–54.6% of control levels and induced substantial apoptosis. Total apoptotic populations reached 52.8–60.1% following BIRC5 knockout and 45.3–50.6% following MADD knockout. Apoptosis induction was confirmed by caspase-3/7 activation, increased Sub-G1 accumulation, and cleavage of apoptosis-related proteins, indicating activation of the intrinsic apoptotic pathway.Notably, BIRC5 disruption consistently produced stronger pro-apoptotic effects than MADD across all cancer models. Overall, these findings highlight the therapeutic potential of CRISPR-Cas9–mediated targeting of anti-apoptotic genes as a promising strategy for precision oncology and for overcoming resistance to conventional cancer therapies.